Analysis and pharmacokinetic study of curdione in Rhizoma Curcumae by UPLC/QTOF/MS. (June 2014) - Lv, Diya; Cao, Yan; Dong, Xin; Chen, Xiaofei; Lou, Ziyang; Chai, Yifeng
ABSTRACT An ultra‐performance liquid chromatography–quadrupole time‐of‐flight/mass spectrometry (UPLC/QTOF/MS) method was established to determine the chemical components of curcuma rhizomes (Ezhu) and their pharmacokinetics. Chromatographic separation was performed by UPLC using a 1.8 µm column in order to obtain good resolution and increase the sensitivity of analysis. Accurate mass measurement within 5 ppm error for each ion produced in positive mode electrospray ionization and the subsequent QTOF product ions enabled 12 compounds to be identified. Several of the identified components, including β‐elemene, curcumol, germacrone and curdione, are thought to be the biologically active ingredients. Quantitative pharmacokinetic analysis was also carried out by UPLC/QTOF/MS. Using 20(S)‐protopanoxadiol as an internal standard, samples were prepared by protein precipitation with methanol. Chromatographic separation was performed on an Agilent Extend‐C18 column (2.1 × 50 mm, 1.8 µm) with acetonitrile (0.1% formic acid)–water (0.1% formic acid) for gradient elution. Curdione calibration plots were linear over the range of 0.1–12.2 µg/mL for curdione in plasma with the lower quantification limit being 6.5 ng/mL, and the recovery from plasma was about 105.2%. The RSD for both intra‐ and inter‐day precision was <9.9%. Copyright © 2014 John Wiley & Sons, Ltd.